Modeling metal deposition in heat transfer analyses of additive manufacturing processes - Michaleris, Panagiotis (Finite elements in analysis and design, 2014)
Additive Manufacturing (AM) processes for metallic parts using both laser and electron beam heat sources are becoming increasingly popular due to their potential of producing near net shape structural components. The thermal history generated by additive manufacturing is essential in determining the resulting microstructure, material properties, residual stress, and distortion. In this work finite element techniques for modeling metal deposition heat transfer analyses of additive manufacturing are investigated in detail. In particular, both quiet and inactive element activation are reviewed in detail and techniques for minimizing errors associated with element activation errors are proposed. 1D and 3D numerical examples are used to demonstrate that both methods can give equivalent results if implemented properly. It is also shown that neglecting surface convection and radiation on the continuously evolving interface between active and inactive elements can lead to errors. A new hybrid quiet inactive metal deposition method is also proposed to accelerate computer run times. •FEA techniques for modeling metal deposition in additive manufacturing are investigated.•A new hybrid inactive/quiet element method is proposed for modeling additive manufacturing.•Metal deposition element is initially inactive, then, they are switched to quiet layer by layer.